IMPLEMENTATION OF THE FOOD ESTATE OF THE GOVERNMENT OF THE REPUBLIC OF INDONESIA IN RIARIA VILLAGE, HUMBANG HASUNDUTAN REGENCY - Adha, Rifki; Bengkel, Bengkel; Nasution, Indra Kesuma (International Journal of Cultural and Social Science, 2025)
Food Estate is not a new term in Indonesia. Food Estate is a policy made by the government to maintain the stability and food security of the country during the food crisis that emerged when the Covid-19 Pandemic emerged. This paper aims to analyze the implementation pattern of the Food Estate policy in Riaria Village, Humbang Hasundutan Regency and its impact on the social, economic and political aspects of the local farming community. The study used a qualitative approach with a descriptive method. Data were collected through in-depth interviews with key informants, field observations and analysis of policy documents. The Food Estate policy is top-down and does not involve the participation of the community and local farmers. The government determines commodities such as shallots and potatoes that are not in accordance with local agricultural habits such as andaliman, frankincense, and coffee, which causes crop failure and economic losses. Labor restructuring, which disrupts gender roles and household food security, is an example of a social impact. Politically, this policy triggers agrarian conflicts and strengthens the power relations between the government, corporations, and farmers. The principles of food sovereignty and community participation are often ignored when the Food Estate is implemented in Ria-Ria Village. This policy increases farmers' dependence on corporations and endangers the local agricultural system. Strengthening farmer institutions, bottom-up approaches, and increasing transparency are some of the policy recommendations.